2019
DOI: 10.1093/aob/mcz052
|View full text |Cite
|
Sign up to set email alerts
|

A case study on the re-establishment of the cyanolichen symbiosis: where do the compatible photobionts come from?

Abstract: Background and Aims In order to re-establish lichen symbiosis, fungal spores must first germinate and then associate with a compatible photobiont. To detect possible establishment limitations in a sexually reproducing cyanolichen species, we studied ascospore germination, photobiont growth and photobiont association patterns in Pectenia plumbea. Methods Germination tests were made with ascospores from 500 apothecia under diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
(58 reference statements)
2
6
0
Order By: Relevance
“…According to the core-fringe species hypothesis (Rikkinen et al 2002), sexual lichen species (fringe) depend on the dispersal of suitable photobionts by asexual species (core). This hypothesis has been supported by recent studies (Belinchón et al 2015;Cardós et al 2019).…”
Section: Introductionsupporting
confidence: 69%
“…According to the core-fringe species hypothesis (Rikkinen et al 2002), sexual lichen species (fringe) depend on the dispersal of suitable photobionts by asexual species (core). This hypothesis has been supported by recent studies (Belinchón et al 2015;Cardós et al 2019).…”
Section: Introductionsupporting
confidence: 69%
“…Using a larger data set, Stenroos et al (2006) found Nostoc photobiont strains to be correlated with mycobiont identity rather than ecological guild. However, fungal preference for the Nostoc photobiont strains of other community members over those sampled from the substratum has been reported in other lichen communities (Cardós et al 2019). In other studies, involving Pannaria and other cyanophilic lichens, both corticolous and saxicolous species sometimes chose closely related strains of Nostoc, and more complex combinations of variable mycobiont selectivity and ecological factors were observed (Elvebakk et al 2008).…”
Section: Cyanobacteriamentioning
confidence: 97%
“…Many studies stress the intrinsic compatibility requirements of individual fungal taxa as primary determinants of pairing patterns (Yahr et al 2004;Stenroos et al 2006;Myllys et al 2007;Leavitt et al 2015;Joneson & O'Brien 2017), often in conjunction with ecological factors (Elvebakk et al 2008;O'Brien et al 2013;Dal Grande et al 2018;Jüriado et al 2019;Pino-Bodas & Stenroos 2020). In some communities, mycobionts may have adapted to utilize a common pool or pools of photobionts, whose local availability might thereby be sustained for all users (Beck et al 2002;Rikkinen et al 2002;Rikkinen 2003;Sanders et al 2016;Onuţ-Brännström et al 2018;Cardós et al 2019). Thallus growth form may also affect photobiont selection patterns.…”
Section: Patterns Of Symbiont Pairingmentioning
confidence: 99%
“…Nutrient content in lichens is tightly determined by the amount of atmospheric nutrients (Johansson et al 2010) and, consequently, high levels of atmospheric nitrogen may increase the %N in lichens without nitrogen‐fixing photobionts. However, the increase of the relative abundance of cyanolichens, with nitrogen fixation ability and higher %N, may depend on the availability of compatible photobionts (Cardós et al 2019) rather than on the atmospheric nutrient deposition.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of variation explaining the species turnover was relatively low (i.e., 1.5–9.2%), which may be partially explained by the low relative contribution of species turnover to the community‐level variation in most studied traits. Furthermore, those traits with a relatively high contribution of species turnover are related with the type of photobiont and the atmospheric nutrient availability, suggesting that factors such as the availability of compatible photobionts, the level of specificity for the photobiont, and nitrogen deposition affect species turnover more than climate does (Cardós et al 2019, Johansson et al 2010). The species turnover may also respond to biotic interactions of competition and facilitation, and to the dispersal capacity and effective local establishment of different species due to their reproductive strategy (Prieto et al 2017).…”
Section: Discussionmentioning
confidence: 99%